2012
DOI: 10.1186/1742-4755-9-4
|View full text |Cite
|
Sign up to set email alerts
|

Health services for reproductive tract infections among female migrant workers in industrial zones in Ha Noi, Viet Nam: an in-depth assessment

Abstract: BackgroundRural-to-urban migration involves a high proportion of females because job opportunities for female migrants have increased in urban industrial areas. Those who migrate may be healthier than those staying in the village and they may benefit from better health care services at destination, but the 'healthy' effect can be reversed at destination due to migration-related health risk factors. The study aimed to explore the need for health care services for reproductive tract infections (RTIs) among femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…The consultation rate was low, which was considered to be due to the reduced concern, long working hours, high costs, long distances between home and work, lack of health information, and ineffective collaboration between local health systems and commercial enterprises. [13,30] In this study, the highest prevalence for MSDs occurred in the neck, shoulders and upper back areas. In a previous study, Yu et al [8] showed that the lower back, neck, shoulders, and wrists were the most common sites for MSDs.…”
Section: Discussionmentioning
confidence: 65%
“…The consultation rate was low, which was considered to be due to the reduced concern, long working hours, high costs, long distances between home and work, lack of health information, and ineffective collaboration between local health systems and commercial enterprises. [13,30] In this study, the highest prevalence for MSDs occurred in the neck, shoulders and upper back areas. In a previous study, Yu et al [8] showed that the lower back, neck, shoulders, and wrists were the most common sites for MSDs.…”
Section: Discussionmentioning
confidence: 65%
“…The result showed that underlying health problems were common among industrial workers (Pham et al, 2019;Tran et al, 2019b;Tran et al, 2019c), with many suffering occupational diseases (Quynh Nguyen et al, 2017;Tran et al, 2016) and/or work-related injuries (Marucci-Wellman et al, 2010;Phung et al, 2008;Ratnasingam et al, 2012). A high prevalence of respiratory system problems was also reported (Chien et al, 2002). Selftreatment (without medication) was found to be the most used method when having health problems (by 28.2-51% of participants), followed by visiting commune health centers (24%) and self-medication (20.3%).…”
Section: Resultsmentioning
confidence: 95%
“…In recent years, female migration has risen [4,15,16], and females are considered to be more vulnerable than male migrants [4]. Research indicates that most female migrants migrate to metropolitan cities before marriage, when they are between 15–34 years old [5,12,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors report that unmarried female migrants are usually poorly educated, lack SRH-related information, and know little about self-protection. However, female migrants often hold open attitudes to premarital sex [3,15,19,20,21,22]. Unsafe sex leads to unintended pregnancy, abortions, pregnancy-related syndromes, and infectious diseases [17,23].…”
Section: Introductionmentioning
confidence: 99%